Identification of functional domains on human interleukin 10 - Gesser, Borbala (The National Academy of Sciences of the USA, 1997)
Interleukin 10 (IL-10) is a recently described natural endogenous immunosuppressive cytokine that has been identified in human, murine, and other organisms. Human IL-10 (hIL-10) has high homology with murine IL-10 (mIL-10) as well as with an Epstein–Barr virus genome product BCRFI. This viral IL-10 (vIL-10) shares a number of activities with hIL-10. IL-10 significantly affects chemokine biology, because human IL-10 inhibits chemokine production and is a specific chemotactic factor for CD8+ T cells. It suppresses the ability of CD4+ T cells, but not CD8+ T cells, to migrate in response to IL-8. A nonapeptide (IT9302) with complete homology to a sequence of hIL-10 located in the C-terminal portion (residues 152–160) of the cytokine was found to possess activities that mimic some of those of hIL-10. These are: (i) inhibition of IL-1β-induced IL-8 production by peripheral blood mononuclear cell, (ii) inhibition of spontaneous IL-8 production by cultured human monocytes, (iii) induction of IL-1 receptor antagonistic protein production by human monocytes, (iv) induction of chemotactic migration of CD8+ human T lymphocytes in vitro, (v) desensitization of human CD8+ T cells resulting in an unresponsiveness toward rhIL-10-induced chemotaxis, (vi) suppression of the chemotactic response of CD4+ T human lymphocytes toward IL-8, (vii) induction of IL-4 production by cultured normal human CD4+ T cells, (viii) down-regulation of tumor necrosis factor-α production by CD8+ T cells, and (ix) inhibition of class II major histocompatibility complex antigen expression on IFN-γ-stimulated human monocytes. Another nonapeptide (IT9403) close to the NH(2)-terminal part of hIL-10 did not reveal cytokine synthesis inhibitory properties, but proved to be a regulator of mast cell proliferation. In conclusion, we have identified two functional domains of IL-10 exerting different IL-10 like activities, an observation that suggests that relatively small segments of these signal proteins are responsible for particular biological functions.